2022
DOI: 10.1177/03946320221096207
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory biomarker predictors for disease progression and outcome among Egyptian COVID-19 patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic resulted in more than five hundred million infected cases worldwide. The current study aimed to screen the correlation of different laboratory findings with disease severity and clinical outcomes of coronavirus disease (COVID-19) among Egyptian patients to obtain prognostic indicators of disease severity and outcome. A total of 112 laboratory-confirmed COVID-19 patients were examined. According to the severity of the disease, these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Lactate dehydrogenase plays a vital role in biochemical processes; it takes part in the inter-conversion of pyruvate, the final product of glycolysis to lactate without sufficient oxygen supply [ 29 , 30 ]. Elevated LDH activity indicates a lack or deficiency of oxygen in biochemical processes, tissue oxygen deficiency, or multi-organ failure [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase plays a vital role in biochemical processes; it takes part in the inter-conversion of pyruvate, the final product of glycolysis to lactate without sufficient oxygen supply [ 29 , 30 ]. Elevated LDH activity indicates a lack or deficiency of oxygen in biochemical processes, tissue oxygen deficiency, or multi-organ failure [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous observational studies have reported several other inflammatory or coagulation-related makers for the prediction of prognostic outcomes in patients contracting COVID-19 [ 49 , 50 ], our meta-analysis is the first to investigate the association of the F/A ratio with poor prognosis. A previous meta-analysis involving more than two thousand patients revealed significantly higher CRP levels among those who succumbed to COVID-19 than in survivors [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with lower platelet-monocyte aggregates might have a higher risk of thrombosis and severe pneumonia. In addition, our results showed that other severity markers were associated with platelet-monocyte aggregates, including lymphocyte count [31], lactate dehydrogenase, and IL-6 [32].…”
Section: Discussionmentioning
confidence: 53%